Oral delivery of insulin via polyethylene imine-based nanoparticles for colonic release allows glycemic control in diabetic rats. (August 2016) - Salvioni, Lucia; Fiandra, Luisa; Del Curto, Maria Dorly; Mazzucchelli, Serena; Allevi, Raffaele; Truffi, Marta; Sorrentino, Luca; Santini, Benedetta; Cerea, Matteo; Palugan, Luca; Corsi, Fabio; Colombo, Miriam
Graphical abstract: Abstract: In this study, insulin-containing nanoparticles were loaded into pellet cores and orally administered to diabetic rats. Polyethylene imine-based nanoparticles, either placebo or loaded with insulin, were incorporated by extrusion and spheronization technology into cores that were subsequently coated with three overlapping layers and a gastroresistant film. The starting and coated systems were evaluated in vitro for their physico-technololgical characteristics, as well as disintegration and release performance. Nanoparticles-loaded cores showed homogeneous particle size distribution and shape. When a superdisintegrant and a soluble diluent were included in the composition enhanced disintegration and release performance were observed. The selected formulations, coated either with enteric or three-layer films, showed gastroresistant and release delayed behavior in vitro, respectively. The most promising formulations were finally tested for their hypoglycemic effect in diabetic rats. Only the nanoformulations loaded into the three-layer pellets were able to induce a significant hypoglycemic activity in diabetic rats. Our results suggest that this efficient activity could be attributed to a retarded release of insulin into the distal intestine, characterized by relatively low proteolytic activity and optimal absorption.